Clothes That Are Not Worn (except...): The Politics of the Clothing Collection at the Museum of Anthropology - Johnson, Elizabeth Lominska (Material Culture Review, 2002)
During the past quarter century, political changes in Canadian society have been reflected in a movement towards more equal relationships between museums and the people represented through their collections. This has been a time of reflection and negotiation, resulting in a very different kind of curatorial practice, one that attempts to respect and include the knowledge and wishes of the people represented. The political relationships around the clothing held in museum collections are particularly sensitive because of the close association of clothing with people. Résumé Depuis vingt-cinq ans, les changements politiques survenus dans la société canadienne se reflètent dans la tendance manifeste vers des relations plus égalitaires entre les musées et les groupes de personnes représentés dans leurs collections. Cette période en a été une de réflexion et de négociation, ce qui a entraîné une pratique de conservation très différente, qui s’efforce de respecter les gens représentés et de tenir compte de leurs connaissances et de leurs désirs. Les considérations politiques relatives aux vêtements figurant dans les collections des musées sont particulièrement complexes en raison de l’étroite association des vêtements à des personnes.